2012
DOI: 10.1002/jwmg.488
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing the reaction of mountain goats towards all‐terrain vehicles

Abstract: The increasing popularity of recreational activities in the wild has led to concerns about their potential impacts on wildlife. All‐terrain vehicles (ATVs) often bring people into wildlife habitats, where they may disturb animal populations. We assessed the influence of ATVs on the behavior of mountain goats (Oreamnos americanus) in a long‐term study population at Caw Ridge, Alberta, Canada. We used multinomial models containing environment‐, disturbance‐, and group‐related factors, to evaluate the response of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
17
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 17 publications
0
17
0
Order By: Relevance
“…We used a two-stage process to evaluate extrinsic and intrinsic factors that were related to patterns of migration, (sensu [12], [34]). We examined extrinsic and intrinsic explanatory variables in a 2-step process because we were interested in evaluating the effects environmental variables would have on patterns of migration at the population level, and then how those patterns might be modified by intrinsic variables, which were more specific to each individual.…”
Section: Methodsmentioning
confidence: 99%
“…We used a two-stage process to evaluate extrinsic and intrinsic factors that were related to patterns of migration, (sensu [12], [34]). We examined extrinsic and intrinsic explanatory variables in a 2-step process because we were interested in evaluating the effects environmental variables would have on patterns of migration at the population level, and then how those patterns might be modified by intrinsic variables, which were more specific to each individual.…”
Section: Methodsmentioning
confidence: 99%
“…While helicopter overflights represent one type of disturbance associated with mining activity in our study area other potential types of disturbance include blasting, heavy equipment, and mill site machinery operation. Because blasting and mechanized human travel have also been documented to alter mountain goat behavior and population dynamics (Joslin 1986, St-Louis et al 2013, it is unclear what types of disturbance were most relevant to the observed patterns of habitat avoidance. As such, we concluded that the cumulative disturbance associated with mining activity is responsible for the observed pattern.…”
Section: Mountain Goat Resource Selectionmentioning
confidence: 99%
“…Previous studies have documented negative effects of human and industrial disturbance on mountain goat foraging behavior, movement patterns and population dynamics (Foster and Rahs 1983, Joslin 1986, Côté 1996, Goldstein et al 2005, Côté et al 2013, St-Louis et al 2013, Richard and Côté 2016. In this context carefully understanding and, potentially, mitigating human and industrial disturbance in areas inhabited by mountain goats is important for ensuring sustainable mountain goat populations.…”
mentioning
confidence: 99%
“…In most cases, disturbance impacts are thought to be additive for mountain goats and result in significant changes of behavior, space use, and population dynamics (Foster and Rahs , Joslin ). Mountain goats appear to change their spatial distribution and increase alertness when facing various anthropogenic activities: aircraft flights (Côté , Gordon and Reynolds , Côté et al ), seismic exploration (Joslin ), industrial development (Foster and Rahs ), road traffic (Singer ), all‐terrain vehicles (St‐Louis et al ), and human confrontation (Foster and Rahs ). Buffer areas of 1.5 km to 2.0 km have been used to limit the impact of helicopter and industrial activities on mountain goats (Foster and Rahs , Côté , Mountain Goat Management Team , Cadsand ).…”
mentioning
confidence: 99%
“…Any recreational activity occurring in areas inaccessible to motorized traffic may result in disturbance potentially causing displacement of mountain goats (Mountain Goat Management Team ). Therefore, where recreation and mountain goat habitat overlap, it is important to understand the relationship between them for managed coexistence (Foster and Rahs , Côté et al , St‐Louis et al ).…”
mentioning
confidence: 99%